Effect of Indonesian medicinal plants essential oils on Streptococcus mutansbiofilm - Triana Hertiani; Sylvia Utami Tanjung Pratiwi; Irami Duma Kencana Irianto; Dian Adityaningrum; Budi Pranoto (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
Essential oil’s component such as menthol and eucalyptol were already used as dental plaque inhibitors. In searching of potential dental plaque inhibitor from natural products, a study to explore the potency of essential oils extracted from several Indonesian medicinal plants against planktonic growth and biofilm adherence of S. mutans was performed. A total of 14 essential oils from some selected Indonesian medicinal plants were extractedby steam-hydro distillation. Antibacterial assay was performed against S. mutansby micro dilution technique on nutrient broth media. Biofilm formation inhibition assay was conducted on a flexible U-bottom 96-wells PVC micro plate by using BHI enriched with sucrose 2% at 36.6 °C for 18-24 h. After staining with 1% crystal violet, the optical density was read at 595 nm. A mouthwash commercial product containing essential oil component was used as a positive control. Result showed that the essential oils of C. sintoc exhibited the highest biofilm formation inhibition (IC50 = 0.005%), and Z. officinale showed the highest biofilm degradation with EC50 value of 0.013%. Both were active against bacterial planktonic growth but C. sintocshowed lower MIC90 value (0.6%) in comparison to Z. officinale(0.06%). Meantime, C. citratus was showed promising antibacterial and antibiofilmactivities with MIC90 value of 0.06%, MBC 0.6%, IC50 0.008% and EC50 0.026%. It is concluded that the essential oils of C. citratus, Z. officinaleand C. sintocare potential to be developed as dental plaque inhibitors.Key words: essential oils, antibacterial, biofilm, Streptococcus mutans